Disconnected: Non-Users of Information Communication Technologies. (September 2018) - Hardey, Mariann; Atkinson, Rowland
Growing concern about the impact of constant, mediated connection has often focused on the ways in which technologies contribute to a ubiquitous sense of presence and interaction, and the kind of invasion that this may represent to a sense of self and privacy. Discussion about information communication technologies is increasingly converging around the need for a deepened understanding of their effect on pace of life, methods of work, consumption, and wellbeing. Counter-narratives to overwhelming hyper-connectivity have emerged as a result of these changes. Using qualitative interview data from respondents recruited from across the globe, we focus on the strategies and worldviews of those who explicitly reject the use of any information communication technologies. Our participants relate how, to varying degrees, they have elected to avoid forms of immediate connection and what they identify as the deep advantages and therapeutic benefits of such ways of being. The article responds to rising social anxieties about being locked into information communication technology ecologies and the difficulty of opting out of corporate information-exchange systems. These concerns, we argue, are generating increasing interest in how to manage information communication technologies more effectively or to switch off altogether.